Explorando a tinta digital para a avaliação: análise de traços simples - Pereira Júnior, Cleon Xavier (2015)
Digital ink technology is available in several electronic devices and can bring contributions to the evaluation process as it allows access to information that was not available in assessments carried out using traditional methods. It is particularly interesting in evaluations involving drawings, since it offers an environment quite similar to pencil and paper, with the advantage of allowing process automation. Thus, the first step is to provide resources to capture, store and reproduce the design done. Then, it is necessary to analyze the collected data. However, analysis of drawings is a complex task and focus of several research projects. Thus, as an initial contribution, this work focuses on the analysis of simple traces. In order to explore digital ink as a means of evaluation, a tool was developed to automate the capture, storage and reproduction of drawings, and test the features and limitations of the analysis of digital ink in order to extract relevant knowledge for the evaluator to make decisions. To test the tool, psychological tests were selected, since in this knowledge domain the use of drawings for assessment is widespread. The tool was developed in two stages. The first, more general, offers resources for test application, storage and later playback for an analysis by the evaluator, not providing resources for automatic analysis of results. Though simple, these resources offer a great contribution, because in addition to storing the final result, which can be visualized as an image, it also stores the design process (allowing the evaluator to follow step by step how the test was performed) in addition to storing other information such as time spent to perform certain steps, the use of rubber etc. The second stage of the tool is the analysis of the stored data. This analysis is test dependent, and should be implemented according to it’s evaluation requirements. As a case study, a test, that uses simple traces, was implemented. The result showed that the digital ink has advantages for carrying out evaluations using drawings as a medium, and should be subject to further research aimed at automating tests with more complex drawings.